Smuggled in a suit with hidden pockets: Gujarati culture and contemporary art - Natalwala, Hitesh (Curtin University, 2015)
This historical investigation involves reflective artistic practice concerning the visual culture of Gujarati Indians who left India at the beginning of the twentieth century, settled initially in Africa and then England in the 1960s. I examine the migration through the tailoring of garments and in collage and sculpture. This critiques conventional ethnographic undervaluing of postcolonialism’s dialectic of celebration and trauma.